Evaluation of the Effectiveness of the Nutritious Meal Program as a Public Service Policy in Improving Student Academic Performance in Wonopringgo District - Sri Sarwati; Rini Werdiningsih; Emiliana Sri Pudjiarti (International Journal of Humanities and Social Sciences Reviews, 2025)
This study aims to evaluate the effectiveness of the Nutritious Meal Program as a public service policy in enhancing the academic achievement of elementary school students in Wonopringgo District. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews, participant observation, and documentation across 19 educational institutions participating in the program. Findings reveal that the program has a significant positive impact on students’ nutritional status, learning motivation, and overall academic performance. Improvements were observed in student concentration, attendance, and classroom participation, indicating a direct link between adequate nutrition and cognitive development. Despite these positive outcomes, several challenges were identified. Issues such as delayed meal distribution, inconsistency in the quality and variety of menus, and limited coordination among stakeholders hinder the program’s optimal implementation. Furthermore, the engagement of parents and community members, while beneficial, was found to be uneven across schools, highlighting the need for stronger collaboration mechanisms. The study identifies three key factors that determine the success of the program: the quality of services provided, the managerial capacity of schools to coordinate and monitor implementation, and active participation from both parents and school committees. To address existing barriers, the research recommends enhancing cross-sectoral collaboration among government agencies, improving managerial competence at the school level, and establishing participatory evaluation systems. These measures would ensure program sustainability, responsiveness to local needs, and greater accountability. Overall, the Nutritious Meal Program demonstrates the potential of inclusive and collaborative public service policies in fostering both student well-being and academic achievement. It reflects a practical example of how government-community partnerships can contribute to creating a healthy, equitable, and sustainable educational ecosystem.